TEMPERATURE DEPENDENCE OF THE EFFECTIVE PHOTOGALVANIC CHARACTERISTICS OF SOLAR ELEMENTS - Alinazarova Maxfuza Alisherovna; Toraboyeva Madina (Zeta Repository, 2023)
In this work, expressions for temperature dependence of short-circuit current density, effective voltage, effective current density and effective power of solar cells are presented and theoretically studied.